2013
DOI: 10.1177/0218492312449637
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical characteristics of the thoracic aortic arch in an Asian population

Abstract: Aortic arch anatomical information from an elderly Asian population can be useful for the development of future endovascular devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In fact, the diagnosis of an diameters of the ascending aorta (39.4 ± 6.7 mm) and descending aorta (34.5 ± 7.9 mm) and the arch angle (103.8 ± 25 degrees). 22 Rylski et al 23,24 reported similar geometric changes before and after the onset of acute aortic syndromes, including aortic dilatation and increased aortic tortuosity. Schäfer 17 also demonstrated in patients with elevated aortic stiffness that the wall shear stress and timeaveraged wall shear stress were significantly reduced from zones 1 to 4 and the oscillatory shear index was significantly elevated in zones 0, 1, and 4, which predicted the development of severe aortopathy.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In fact, the diagnosis of an diameters of the ascending aorta (39.4 ± 6.7 mm) and descending aorta (34.5 ± 7.9 mm) and the arch angle (103.8 ± 25 degrees). 22 Rylski et al 23,24 reported similar geometric changes before and after the onset of acute aortic syndromes, including aortic dilatation and increased aortic tortuosity. Schäfer 17 also demonstrated in patients with elevated aortic stiffness that the wall shear stress and timeaveraged wall shear stress were significantly reduced from zones 1 to 4 and the oscillatory shear index was significantly elevated in zones 0, 1, and 4, which predicted the development of severe aortopathy.…”
Section: Discussionmentioning
confidence: 91%
“…Age‐related changes in the aortic geometry, including dilatation of the aorta, a decrease in the curvature of the arch and clear aortic unfolding, contribute to increasing the aortic stiffness . However, compared with healthy elderly individuals in Asian populations, uncomplicated patients with IMHB showed clear changes in the diameters of the ascending aorta (39.4 ± 6.7 mm) and descending aorta (34.5 ± 7.9 mm) and the arch angle (103.8 ± 25 degrees) . Rylski et al reported similar geometric changes before and after the onset of acute aortic syndromes, including aortic dilatation and increased aortic tortuosity.…”
Section: Discussionmentioning
confidence: 91%
“…Aiming to better understand the anatomical characteristic of the aortic arch, lots of studies on the analysis of aortic arch anatomical parameters had been carried out recently, with the study population consisted of patients either with aortic pathology or health controls (22)(23)(24)(25)(26)(27)(28). The most widely applied parameters included the diameter of different aorta segment, the clockwise angle and take off angle of the supra aortic branches, the type of aortic arch and the angle of the aortic curvature and etc.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that the diameter of the aorta as well as the length of aortic arch and the ascending aorta increase with age [ 4 6 ]. Chiu et al proposed an aortic arch measurement [ 24 ]. It requires the designation of a central line and the application of the points of origin of the aortic arch branch vessel.…”
Section: Discussionmentioning
confidence: 99%